Family carers' needs related to management of functional disability in dementia care and use of mHealth applications in health information seeking: An online survey. Issue 3 (June 2020) - Rathnayake, Sarath; Moyle, Wendy; Jones, Cindy; Calleja, Pauline
Abstract: Background: Family carers of people with dementia face different challenges in providing care for daily living activities of their care recipients. Today, mHealth applications are widely used in healthcare. Aim: To examine the needs of family carers of people with dementia concerning the management of functional disability of their care recipients, carer burden and use of mHealth applications when seeking health information. Methods: A total of 166 family carers, who were recruited through leading dementia support organisations in Australia, research institutes, and social media, completed an online survey. In data analysis, descriptive statistics, Pearson's Chi-square test, Mann-Whitney U test and Kruskal-Wallis H test were used. Findings: People with dementia were dependent on family carers for complex activities (e.g. taking medication) (99.4%), domestic activities (e.g. washing clothes) (97%), and self-care (e.g. bathing) (79.5%). Family carers reported a moderate-to-high need for education in functional disability care (62.6%). Bathing was reported as the most difficult activity to perform (30.1%). Three-quarters of carers reported carer burden (74.1%). Most carers (98.8%) owned a smart-device, and 51.2% of family carers reported having an mHealth application. Educational needs for functional disability care were associated with age (highest among those between 36–65 years) and eHealth literacy of carers (greater among carers with adequate eHealth literacy). Carer burden was associated with stage of dementia (highest in advanced dementia) and experiencing chronic medical problems of care recipients. Possession of an mHealth application was associated with employment status (currently employed), adequate eHealth literacy and higher educational needs. Conclusion: Providing functional disability care is one of the priority needs for education. These educational needs can potentially be provided via mHealth applications. Health professionals can use these findings to plan educational interventions to address family carers' needs.